"Biophilia as a Sustainable Design Approach for University Buildings Design: a case study in university campus drawing studios Cairo, Egypt.". Issue 1 (1st December 2022) - Mahrous, Amira M; Dewidar, Khaled M.; Rifat, Mostafa M; Nessim, Ashraf A
Abstract: University campuses have a long history of enriching the social, cultural, and economic value of societies. Worldwide, there is a rising demand for the integration of new approaches into the planning and design of university buildings to further improve their quality. According to the literature, many approaches needed to be considered while designing university buildings that can enhance students' performance. Biophilic design is known to have enhancing levels of interaction, and interaction patterns, enhancing health and wellbeing in terms of physiological, psychological, cognitive, and social/ spiritual benefits, while rigorous scientific evidence that supports such claims is rare. Many researchers have previously investigated the application of biophilic elements in working environments, however limited research is related to university building designs, specifically in Egypt. There is limited research on methods for quantifying the effect of biophilic design patterns on the physiological, and cognitive benefit. Thus, in light of the concept of Biophilia, this research aims to identify the correlations between the biophilic patterns and enhancing student performance. Survey questionnaires were administrated to a sample of students who regularly use the selected drawing studio. The extracted data will be analyzed through the use of SPSS software. This paper will benefit researchers who are interested in this field and may serve as a suitable beginning point for them and designers as well as a guideline while designing a university using biophilic patterns.